Effect of focal and diffuse hypervascularization as cystoscopic findings on predicting intravesical therapy response in patients with bladder pain syndrome - ONUR, AHMET RAHMİ (AVES, 2021)
Objective: To define the relationship between cystoscopic findings, including novel findings such as the hypervascularization, of bladder pain syndrome/interstitial cystitis (BPS/IC) and the response to intravesical therapy. Material and methods: We retrospectively evaluated cystoscopy findings in patients who had a preliminary diagnosis of BPS/IC. All patients received early intravesical combined therapy (ICT), ie, within 2 hours after hydrodistention. Additionally, ICT was continued according to our protocol. Cystoscopic findings were classified as glomerulations, hypervascularization, and Hunner's lesion (HL). The therapy responses were evaluated at 1st, 3rd, 6th, and 12thmonths using the visual analog scale (VAS), O'Leary/Sant interstitial cystitis symptom index (ICSI), and interstitial cystitis problem index (ICPI) scores. Results: Out of 61 patients, HL was diagnosed during cystoscopy in six (9.8%) patients, glomerulations in 35 (57.4%) patients, and hypervascularization in 15 (24.6%) patients. No pathological findings were defined in five (8.2%) patients. In the glomerulation and hypervascularization group, the median VAS, ICSI, and ICPI scores were lower than those in the preoperative period in the follow-up. In patients with HL, the median VAS scores were lower in the entire follow-up compared to the preoperative period, with an increase at 1st year compared to 6th month, and ICSI scores were lower than preoperative period in the entire follow-up, with an increase at 3rd month and 1st year. ICPI scores were also lower during the follow-up, with an increase observed in the 1st year. Conclusion: The presence of hypervascularization should be defined since it might show different characteristics that may affect the ICT response. Patients with glomerulations might be good candidates for early combined intravesical therapy.
Keywords: Bladder pain syndrome; chondroitin sulfate; glomerulations; hyaluronic acid; hypervascularization; interstitial cystitis; CHRONIC PELVIC PAIN; INTERSTITIAL CYSTITIS; SYNDROME/INTERSTITIAL CYSTITIS; SYMPTOMS; WOMEN